A note on interest rate policy during the Great Depression - Matti Virén (Bank of Finland, 1989)
This paper presents some analyses of interest rate determination in six industrialized countries during the Great Depression. The main finding of the paper is that the huge real interest rate shocks experienced during that time were mainly due to policy actions by central banks.
URN:NBN:fi:bof-201807301753
Keywords: 330